Role of Community Leaders in Managing Covid-19 Pandemic in Indonesia - Pascawati, Nur Alvira; Satoto, Tri Baskoro Tunggul; Alamri, Annisa Rizqa (UI Scholars Hub, 2022)
Community leaders must understand their role in controlling COVID-19, such as monitoring misleading information and providing socialization, education, protection, monitoring, and evaluation activities in the community, due to the numerous limitations of local governments in managing large populations during this crisis. This study aimed to describe the role of Yogyakarta community leaders in increasing community engagement in managing the Covid-19 pandemic. This study uses a quantitative method with a cross-sectional approach, and the study sample includes all community leaders as many as 31 people at the levels of neighborhood and hamlet. The data analysis process uses frequency distribution values. Results showed that most community leaders had not been maximal in implementing the following COVID-19 prevention activities in the community: educating the community regarding isolation and self-quarantine, eliminating the negative stigma in suspected, probable, and confirmed cases of COVID-19 in medical personnel, and inviting the community to participate in providing hand-washing facilities in public places and facilities to assist underprivileged/elderly people who live alone. Leaders have also not been maximal in planning the needs of people who carry out self-isolation and appointing volunteers and community representatives to prepare and distribute food, personal hygiene equipment, and logistics. Most of the leaders only use billboards as a means of education. Some supporting activities have not been maximized, namely removing the stigma/anxiety in the presence of people who work as medical personnel. The role of the leader is not optimal in providing supporting infrastructure in implementing health protocols, and removal of the social stigma must be improved through risk communication assistance and empowerment.